ANTIMICROBIAL AND ANTI-INFLAMMATORY ACTIVITIES OF PLEUROSTYLIA CAPENSIS TURCZ (LOES) (CELASTRACEAE). - Razwinani, Mapula; Tshikalange, Thilivhali Emmanuel; Motaung, Shirley C. K. M. (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Pleurostylia capensis is a large tree that can reach the maximum height of 20 m long, and it have been traditionally used as cosmetic, for steam bath, ritual body wash, and as a purgative to treat symptoms of witchcraft. Using ethanol, chloroform, dichloromethane (DCM), ethyl acetate (EA), and water extracts, leaves, bark and roots of Pleurostylia capensis were investigated scientifically for their effectiveness in antimicrobial, antioxidant and anti-inflammatory activities using standard methods Materials and Methods: The extracts were evaluated for antimicrobial activity against Gram positive (Staphylococcus aureus, Bacillus cereus, and Mycobacterium smegmatis), Gram negative (Escherichia coli, Klebsiella pneumonia, Klebsiella oxytoca, Streptococcus pyogenes, Pseudomonas aeruginosa and Salmonella typhimurium), and Candida albicans. The antioxidant activity was investigated using 2, 2-diphenlyl-1-picrylhadrazyl (DPPH), free radical scavenging assay. The anti-inflammatory activity of P. capensis extracts was evaluated against both cyclooxygenase enzymes (COX 1 and 2). Results: The ethyl acetate extracts of P. capensis showed a strong antimicrobial activity against B. cereus, K. pneumonia, S. pyogenes, and M. smegmatis with MIC value of 0.39 and 0.78 mg/ml. While the ethanol bark extract was most active against M. smegmatis with MIC value of 0.78 mg/ml; the least potent activity was observed with dichloromethane, chloroform and water extracts, with an MIC value ranging from 1.56 mg/ml to 50.0 mg/ml. The plant extracts proved to be good antioxidant agent, whereas extracts of ethanol were the most active, with IC50 ranging from 1.00 to 1.74 μg/ml, which is lower, and in close range to Vitamin C (1.40 μg/ml). Conclusions: Its moderation to potent inhibitory activity was observed in all extracts. Ethanol and dichloromethane extracts were among the most potent when compared to water and petroleum ether extracts. The water extracts showed to be nontoxic on the Hek cell line with an IC50 value of 204.0, and 207.3 μg/ml (roots and bark) respectively. The dichloromethane, ethyl acetate, chloroform and ethanol extracts showed to be toxic on the Hek cell, with IC50 range from 5.94 to 42.91μg/ml. The results obtained indicate the effectiveness of these plants.